2006
DOI: 10.1111/j.1365-2052.2006.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for biogeographic patterning of mitochondrial DNA sequences in Eastern horse populations

Abstract: Equine mitochondrial DNA (mtDNA) phylogeny reconstruction reveals a complex pattern of variation unlike that seen in other large domesticates. It is likely that this pattern reflects a process of multiple and repeated, although not necessarily independent, domestication events. Until now, no clear geographic affiliation of clades has been apparent. In this study, amova analyses have revealed a significant non-random distribution of the diversity among equine populations when seven newly sequenced Eurasian popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
60
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 12 publications
11
60
2
5
Order By: Relevance
“…Studies of mitochondrial DNA have shown that modern horses are descended from at least 77 different wild mares, with a last common ancestor over 300,000 years ago, and so probably originated in very different regions (Vilá et al 2001;Jansen et al 2002). Despite this matrilineal genetic diversity, correlations between modern breeds of horses and mitochondrial genotype are uncommon (Jansen et al 2002;Lopes et al 2005;McGahern et al 2006). This is probably because horse-trading and horse-stealing, sometimes over long distances, have been popular and profitable for a long time.…”
Section: Introductionmentioning
confidence: 91%
“…Studies of mitochondrial DNA have shown that modern horses are descended from at least 77 different wild mares, with a last common ancestor over 300,000 years ago, and so probably originated in very different regions (Vilá et al 2001;Jansen et al 2002). Despite this matrilineal genetic diversity, correlations between modern breeds of horses and mitochondrial genotype are uncommon (Jansen et al 2002;Lopes et al 2005;McGahern et al 2006). This is probably because horse-trading and horse-stealing, sometimes over long distances, have been popular and profitable for a long time.…”
Section: Introductionmentioning
confidence: 91%
“…Otherwise, the haplogroup structure of West European breeds with the dominant L (Cieslak et al, 2010) and Bulgarian mountain pony breeds with higher percentage of M and J is also quite different (Hristov et al, 2016). The best congruency can be found to horses from the Middle East (Achilli et al, 2012) with exception of East Anatolian horses (Koban et al, 2012) although the group G has a higher percentage in Kabardian horses at expense of group L. In breeds from Middle East (Ahkal Teke, Caspian), the haplogroup L is dominant followed by a mixture of A/B/G (McGahern et al, 2006a;Cieslak et al, 2010). But overall, the majority of haplotypes and haplogroups are not restricted to a certain geographical area or a specific breed.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…But the very high mitochondrial haplotype diversity in horses is a well-known fact (Cardinali et al, 2016;Gemingguli et al, 2016). Multiple, widespread and repeated domestication of diverse founder mares as well as mixed origin of most breeds are considered as likely causes for this phenomenon (Cozzi et al, 2004;McGahern et al, 2006a;Lei et al, 2009). In agreement with previous studies, only one to three horses share the same haplotype (Cozzi et al, 2004;Lei et al, 2009;Achilli et al, 2012;Bigi et al, 2014).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Recent studies on the origin of the domestic horse have looked at the inter-population distances (Jansen et al 2002;Aberle and Distl, 2004;McGahern et al, 2006). The genetic monitoring of endangered populations is an important issue (Ząbek et al, 2005;Àlvarez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%